Biological factors and production challenges drive significant UK fruit and vegetable loss - Gage, Ewan; Terry, Leon A.; Falagán, Natalia (Wiley, 2025)
BACKGROUND Food loss and waste estimates are highly inconsistent as a result of methodological and systemic differences. Additionally, the absence of in‐depth evidence surrounding the biological drivers of food loss and waste precludes targeted mitigation action. To address this challenge, we undertook a metanalysis utilising a systematic literature review combined with industry stakeholder surveys to examine the incidence of food loss and waste in the UK fruit and vegetable supply chain between primary production and retail. RESULTS We estimated that 37% of fruit and vegetables, equivalent to 2.4 Mt of produce, is lost between production and sale. In the UK, primary production is the main stage responsible for these losses (58%), and is dominated by four crops (apple, onion, carrot and potato), which contribute 71% of total food loss and waste. Quality and supply/demand mismatch are the core drivers, combined with limited ability to control postharvest quality decline as a result of technical or economic barriers. CONCLUSIONS Innate biological mechanisms contribute to, and detract from, marketable quality generating food loss risks where these cannot be adequately modified or controlled. Through climate change effects, reduced pesticide availability, changing consumer behaviour and increased pressure to reduce resource/energy inputs during pre‐ and postharvest handling, food loss and waste risk is likely to increase in the short term unless targeted, coordinated action is taken to actively promote its mitigation.
Keywords: nutrition; challenge; climate change; sustainability; food security; 30 Agricultural, Veterinary and Food Sciences; 3008 Horticultural Production; Cancer; 2 Zero Hunger; 12 Responsible Consumption and Production; Food Science